ANALISIS FRAMING MEDIA ONLINE DALAM PEMBERITAAN PROFIL DAN KEBIJAKAN MENTERI SUSI PUDJIASTUTI (Studi Pada Situs Berita Detik.com, Kompas.com dan Antaranews.com periode Oktober - Desember 2014) - Tari Suprobo; Royke Siahainenia; Dewi Kartika Sari (Universitas Kristen Satya Wacana, 2016)
Susi Pudjiastuti is part of Jokowi-JK Cabinet that became controversial because of her profile and policy. She is women ministry that having tatoo, smoker and only graduated from junior high school, on the other side her policy to sinking and burst illegal ship which steal fish in Indonesia ocean make some pro-contra. This research are focuses on how online media construct Susi’s profile and policy on 3 popular online media detik.com, kompas.com and antaranews.com using Pan Kosiscki framing analysis model.The result showed that each media has their own way to construct Susi’s news. Detik.com describe Susi as a succses entrepreneuer without high education and her policy to burst illegal ship is legal to do it. Kompas.com describe Susi as a “nyentrik” minister and she still burst illegal ship altough created pro-contra. Antaranews.com describe Susi as a competent women and her policy to burst illegal ship is an explicit action to give lesson.Keywords : Menteri Susi, Profil, Kebijakan, Framing, Media Online